Synergy Improves Literature and Inclusion Indonesian Islamic Bank - Dewi Kirowati; Iwan Suhasto; Shinta Anggraeny (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
Based on OJK data, the literacy index ranges from 8.93% or far below the conventional bank index, which is 38.03%. Meanwhile, the Islamic financial inclusion index only reached 9.1% or below the conventional bank index of 76.19%. Low financial literacy results in the development of the stock market of the Islamic financial services industry being relatively small, which is only 9.9% of the assets of the national financial industry. Therefore, by looking at the literacy and inclusion index problem of Bank Syari^ah Indonesia, in this study the researcher aims to find out what synergy is being done in increasing financial literacy and inclusion of Bank Syari^ah Indonesia. The type of research used is qualitative research, using descriptive methods. In this research, the data collection technique used is observation and literature study and the data presented in descriptive form without being processed by data reduction analysis techniques, data presentation, and drawing conclusions. This research is expected to provide information about the synergy to increase financial literacy and inclusion at Bank Syari’ah Indonesia.